Implementasi Sistem Monitoring Sparepart Berbasis Web Menggunakan Metode Waterfall (Study Kasus : PT. Indomax Ascarya Machinery) - Rizky Darmawan, M.; Awaludin, Fahmi; Haryono, Wasis (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
This research aims to design and implement a web-based spare parts monitoring system using the Waterfall method. The study identifies inefficiencies in the current manual system at PT. Indomax Ascarya Machinery, such as data mismanagement and operational delays. By adopting the Waterfall method, a systematic approach is applied, including stages of requirements analysis, system design, implementation, testing, and maintenance. The system was validated through Black Box Testing, ensuring that the functionalities align with the company's needs. The findings highlight significant improvements in operational efficiency, accuracy in inventory management, and ease of data access. This system provides a foundation for broader digital transformation efforts in the company.